Accessibility of Information and Communication Technology Services by Faculty Members of a State Agricultural University - Ziaulhaq Haqyar; Anil Kumar Rohila; Rati Mukteshawar, Joginder Singh Malik, Ram Niwas (Indian Journal of Extension Education, 2022)
The research was carried out at the CCS Haryana Agricultural University, Hisar in 2021- 22 to assess the availability and accessibility of information and communication technology services among faculty members. Data was collected with the help of a well-structured questionnaire and analyzed using Statistical Package for the Social Sciences (SPSS). 25 faculty members were selected randomly from four purposively selected colleges of CCSHAU, Hisar. The study concluded that all of the respondents had computer/laptop, internet, e-mail, and mobile phone/ telephone facilities available at the department/workplace. The majority of the respondents also had printers (97.00%), scanners (83.00%), photocopiers (77.00%) and LCD projectors (74.00%).